Experimental and numerical analysis of heat convection in cylindrical composite structures with internal defects. (18th October 2019) - Muc, Aleksander; Chwał, Małgorzata; Stawiarski, Adam
The present article discusses the influence of delamination and external loads on the heat transfer in flat and curved laminated panels. Three cases are considered in details: (1) the unloaded structure (length is a constant), (2) the static loading, and (3) the fatigue loading. Here, the comparison between experimental and numerical (finite element method) results is presented. The numerical model allows us to adopt implementations of various boundary conditions as well as the size of delamination. The influence of the shallowness parameter and the thermal resistance is demonstrated. The experimental detection of temperature contours during the cooling process has been conducted at different points in the area surrounding the delamination.